REMARKS ON SOME CONTEMPORARY PERFORMANCES OF EPICS IN THE MPR: БНМАУ дахь орчин үеийн туульс хайлахад хийсэн ажиглалт - .Б, Мөнхцэцэг; C. R. Bawden (Acta Mongolica, 2013)
C. R. Bawden vsrote the research paper on “Remarks on some contemporary * performances of epics in the MPR" Die mongolischen Epen: Bezbge, Sinndeutung und bberlieferung, ed. The paper is based on the relationship between epic structure and performance, visiting during fieldwork in Mongolia during the period September to December 1967. This paper presents the different performances of Mongolian bards of different ethnic groups, the features of the Mongolian epics and four types of delivery. He tried to describe the mode of delivery ofthe epic include the words xailax and xuurnex.